OCCUPATIONAL HEALTH ALARM FOR SOFTWARE EMPLOYEES –A REVIEW - SEKAR BABU HARIRAM; G.MRUGA BOOPATHY; CHANDRAN MASI; S.THENESH KUMAR (International Journal of Pharma and Bio Sciences, 2013)
The present work has been reviewed to enlighten the possible occupational diseases the IT professionals prone to get. The type of work pressure and its impact on various organs leads to several complications are very well advocated. Health complications such as, the psychosomatic disease, heart ailments, neurological diseases, digestive disorders, ENT and infertility problems are faced by both male and female software employees. Hence this type of study is aimed to enlighten the prophylactic measures to be followed by the software employees to avoid the occupational diseases. The study can be further extended to screen the type of diseases they are prone to get according to the years of service with the help of medical practioner.